Pengaruh Kompetensi Sumber Daya Manusia dan Budaya Organisasi terhadap Pencegahan Kecurangan Pengelolaan Dana BLT pada Masa Pandemic Covid-19 - Ahmad Imron Hidayat; Mayar Afriyenti (Universitas Negeri Padang, 2023)
This study aims to prove and analyze the effect of human resource competence and organizational culture on the prevention of fraud in the management of BLT funds during the Covid 19 Pandemic in Padang City. In this study, a sample of 208 respondents were officers who distributed BLT funds to beneficiary communities who had been registered by related parties. The process of collecting data and information is done by distributing questionnaires. The process is carried out through field observations involving researchers directly. The data analysis method used is OLS multiple regression analysis and t-statistical testing. Based on the results of hypothesis testing, it was found that human resource competence and organizational culture had a positive effect on preventing fraud in the management of BLT funds during the Covid 19 pandemic.